Participation of the sultanate of ternate in the unitary state of Indonesia - Rusdi Hasan, Oktosiyanti MT. Abd Rustam Hasim (Opción, 2019)
This paper aims to reconstruct the political participation ofSultanate of Ternate in the Unitary State of Republic of Indonesia afterindependence in 1945. The method used in this paper is a historicalmethod, namely heuristics, criticism, interpretation, andhistoriography. As a result, the State of East Indonesia (NegaraIndonesia Timur or NIT) was formed and covered Sulawesi region, theLesser Sunda (Bali and Nusa Tenggara) and Moluccas Islands. Inconclusion, peace, justice, and prosperity, are the keywords that howimportant the nobility is, in the eyes of the people.